O135 Sensory evoked potentials and central motor conduction times in children with dystonia help predict outcomes from Deep Brain Stimulation (DBS). Issue 9 (September 2017) - McClelland, Verity; Fialho, Doreen; Flexney-Briscoe, Denise; Holder, Graham; Elze, Markus; Gimeno, Hortensia; Siddiqui, Ata; Selway, Richard; Mills, Kerry; Lin, Jean-Pierre
Abstract : Objectives: Deep Brain Stimulation (DBS) of the Globus Pallidus Internus produces dramatic benefits in primary dystonia. Improvements in patients with secondary dystonia are smaller and vary markedly between individuals. Predictive markers are lacking. This study tests the hypothesis that Somatosensory Evoked Potentials (SEPs) and Central Motor Conduction Times (CMCT) may predict outcome from DBS in childhood dystonia. Methods: Data were obtained from 180 consecutive children with dystonia undergoing multidisciplinary assessment for DBS (mean age 10 years; range 2.5–19). CMCT to each limb was obtained using Transcranial Magnetic Stimulation and the F -wave method. Median and posterior tibial nerve SEPs were recorded over contralateral and midline centro-parietal scalp. Technically unsatisfactory data were excluded. Structural abnormalities were assessed with cranial MRI. Outcome from DBS at 1 year was assessed as percentage improvement in Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS-m). Results: Satisfactory CMCT data were obtained from 146 children, of whom 28 (19%) had an abnormal CMCT to at least one limb. Satisfactory cortical SEP data were obtained from 100 children, of whom 47 had at least one abnormal cortical potential. Abnormal CMCTs and SEPs were both observed more frequently in secondary than primary/primary plus dystonia (CMCT abnormal in 22% secondary versus 9% primary patients; SEP abnormal in 53% secondary vs 24% primary patients). Of children proceeding to DBS, improvement in BFMDRS-m was greater in those with normal ( n = 78) than abnormal CMCT ( n = 11) (Mann Whitney test p = 0.002) and was also greater in those with normal ( n = 35) versus abnormal SEPs ( n = 16) (Mann Whitney test p = 0.001). On sub-group analysis, the relationships between CMCT/SEPs and BFMDRS-m scores were independent of aetiology (primary versus secondary) and MRI findings (normal versus abnormal). Discussion/Conclusion: CMCTs and SEPs provide objective evidence of motor and sensory pathway dysfunction in children with dystonia and relate to DBS outcome. These markers may therefore contribute to patient selection and counselling of families about potential benefit from neuromodulation. Significance: We identify neurophysiological markers that can guide the selection of patients for DBS.